Technology and Development: Stylized Facts and Policy Directions - Dadush, Uri (2012)
The adoption of technologies from abroad is a necessary component of rapid and sustained growth in developing countries, enabling them to catch up with the more advanced economies. The speed at which technology is adopted depends essentially on a country's own efforts--there are few external impediments to the spread of most technologies. Contributing outright "new to the world" innovations is unlikely to be an important part of this process for developing countries, though creative adaptation of preexisting technologies can be necessary and valuable. Thus, much of the technology gap relates not to new technologies but to older technologies and the failure to spread them widely within developing countries. Newer technologies are spreading increasingly rapidly, partly because they generally require less infrastructure investment and because government involvement is facilitating quicker access to disadvantaged regions within countries. A sound development strategy should include a concerted effort to import technology and be based on three pillars. The first two pillars are openness and absorptive capacity (education, investment climate) and are essential pursuits on their own merits. The third pillar is more controversial and involves direct intervention to deal with market failures that impede technology diffusion. Success in this difficult area depends on the quality of execution as well as on the design of policies, and avoiding their capture by special interests. Many developing countries have demonstrated that they can catch-up rapidly, and yet the technology frontier continues to push outward and the gap between the developing and industrial countries remains significant--pointing to their still largely untapped potential.